2007
DOI: 10.1371/journal.pgen.0030194
|View full text |Cite
|
Sign up to set email alerts
|

The GLUT9 Gene Is Associated with Serum Uric Acid Levels in Sardinia and Chianti Cohorts

Abstract: High serum uric acid levels elevate pro-inflammatory–state gout crystal arthropathy and place individuals at high risk for cardiovascular morbidity and mortality. Genome-wide scans in the genetically isolated Sardinian population identified variants associated with serum uric acid levels as a quantitative trait. They mapped within GLUT9, a Chromosome 4 glucose transporter gene predominantly expressed in liver and kidney. SNP rs6855911 showed the strongest association (p = 1.84 × 10−16), along with eight others… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
203
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(217 citation statements)
references
References 25 publications
9
203
0
5
Order By: Relevance
“…Indeed, genome-wide association studies found that the major locus associated with uric acid plasma levels in human cohorts was the SLC2A9 gene, explaining up to 3.5% of serum uric acid level variations (93). This initial study was rapidly followed by several similar reports that replicated, in other cohorts, the observed association of SLC2A9 with uricemia and demonstrated that human GLUT9 is a urate transporter (69,(94)(95)(96)(97).…”
Section: Figurementioning
confidence: 87%
“…Indeed, genome-wide association studies found that the major locus associated with uric acid plasma levels in human cohorts was the SLC2A9 gene, explaining up to 3.5% of serum uric acid level variations (93). This initial study was rapidly followed by several similar reports that replicated, in other cohorts, the observed association of SLC2A9 with uricemia and demonstrated that human GLUT9 is a urate transporter (69,(94)(95)(96)(97).…”
Section: Figurementioning
confidence: 87%
“…Brandstatter et al 5 report strong associations with serum urate for rs6855911, rs644921 and rs7442295 in Bruneck study. Associations were reported for rs6855911 and rs7442295 in SardiNIA and InCHIANTI cohorts 6 and Wallace et al 7 reported an association for rs7442295 in the GRAPHIC, BRIGHT and TwinsUK cohorts. In each of these studies, A QTL for serum urate at 4p15 N Cummings et al consistent with our study results, the direction of the effect showed decreased serum urate levels with each copy of the minor allele and P-values for association with urate ranged from 10 À9 to 10 À13 .…”
Section: Discussionmentioning
confidence: 98%
“…Notably, recent genome-wide association studies have identified a strong positional candidate gene, SLC2A9, in this region. [5][6][7] In this study, we aim to characterize the genetic variation contributing to the linkage signal observed at 4p15.3 by single nucleotide polymorphism (SNP) genotyping the positional candidate SLC2A9 in the Mauritius Family Study population. The Mauritius Family Study focuses on large family pedigrees from a subset of the Mauritian population to minimize heterogeneity and environmental effects.…”
Section: Introductionmentioning
confidence: 99%
“…Recent genetic studies revealed a strong link between urate plasma levels and single nucleotide polymorphisms in the SLC2A9 gene encoding Glut9, a member of the glucose transporter family highly expressed in liver and kidney (15,(16)(17)(18). At least two splice variants have been identified differing only in the length of their amino-terminal cytoplasmic domains.…”
mentioning
confidence: 99%